Pemberian Pijat Kaki (Foot Massage) untuk Mengatasi Masalah Keperawatan Resiko Perfusi Cerebral Tidak Efektif pada Hipertensi - Arnifa, Erlin Dewi; Wulandari, Tri Suraning (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Hypertension is a disease of the cardiovascular system with an increase in blood pressure both systole and diastole above 140/90 mmHg. One of the nursing problems that often occurs in patients with hypertension is the risk of ineffective cerebral perfusion which can result in decreased oxygen supply to the brain. This descriptive qualitative case study research aims to determine the effectiveness of non-pharmacological therapy in the form of foot massage on the problem of ineffective cerebral perfusion risk in two hypertensive subjects. Data were collected through interviews, observations, and physical examinations. Foot massage intervention with pressing and twisting techniques at certain points on the soles of the feet for 25 minutes per day was given for three consecutive days. The results showed that after the foot massage intervention, the first subject (Mrs M) had a decrease in blood pressure from 158/96 mmHg to 143/87 mmHg with improvement in symptoms such as headache and anxiety. In the second subject (Mr M), blood pressure dropped from 156/93 mmHg to 147/86 mmHg with similar symptom improvement. It can be concluded that the provision of foot massage can effectively improve the risk of ineffective cerebral perfusion problems in patients with hypertension by lowering blood pressure and improving symptoms experienced.